A PENGEMBANGAN MEDIA MYSTERY BOX UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG PADA PESERTA DIDIK KELAS I SEKOLAH DASAR - Saryandi, Saryandi; Yuhana, Yuyu; Vivi Yandari, Indhira Asih; Alamsyah, Trian Pamungkas (Jurnal Pendidikan Dasar, 2024)
Mystery Box is a media for learning numeracy that is currently popular and suitable for use in learning numeracy skills. This research aims to determine the process of developing the Mystery Box media, to determine the feasibility of the learning media and students' responses to the Mystery Box media and to determine the improvement in numeracy skills in class I elementary school students. This research was conducted at Az-Zahra Elementary School. Data collection techniques in this research are interviews, observation, questionnaires and documentation. The research and development method uses a research and development research design by Borg & Gall which was developed by Sugiono, namely potential and problems, data collection, product design, product validation, design revision, and product trials (limited trials). Based on validation by material experts, they obtained an average percentage score of 79% in the "Decent" category, validation by media experts obtained an average percentage score of 82% in the "Very Appropriate" category. The accumulated validation results of the Mystery Box learning media obtained an average percentage score of 80.5% in the "Decent" category. The results of product trials (limited trials) on 20 class I students at Az-Zahra Elementary School obtained an average percentage score of 92.50% in the "Very Eligible" category. Based on the results of research and development, it can be concluded that the Mystery Box learning media is very suitable and very good for use in learning numeracy skills in class I elementary school.